Reversible, cooperative reactions of yeast vacuole docking - Jun, Youngsoo (2006)
Homotypic yeast vacuole fusion occurs in three stages: (i) priming reactions, which are independent of vacuole clustering, (ii) docking, in which vacuoles cluster and accumulate fusion proteins and fusion regulatory lipids at a ring-shaped microdomain surrounding the apposed membranes of each docked vacuole, where fusion will occur, and (iii) bilayer fusion/compartment mixing. These stages require vacuolar SNAREs, SNARE-chaperones, GTPases, effector complexes, and chemically minor but functionally important lipids. For each, we have developed specific ligands that block fusion and conditions that reverse each block. Using them, we test whether docking entails a linearly ordered series of catalytic events, marked by sequential acquisition of resistance to inhibitors, or whether docking subreactions are cooperative and/or reversible. We find that each fusion protein and regulatory lipid is needed throughout docking, indicative of a reversible or highly cooperative assembly of the fusion-competent vertex ring. In accord with this cooperativity, vertices enriched in one fusion catalyst are enriched in others. Docked vacuoles finally assemble SNARE complexes, yet still require physiological temperature and lipid rearrangements to complete fusion.